Empirical Evaluation of Maintainability Index Accuracy for Measuring Maintainability of Python Programs - Morrison, Rachael; Wedyan, Fadi; Abuomar, Osama Sam (2023 Tenth International Conference on Software Defined Systems (SDS), 2023)
The Maintainability Index is a well-known software metric that is commonly used to measure the maintainability of software. However, it has some potential issues due to its origin and components. In this paper, we empirically evaluate the accuracy of the maintainability index as a measure of maintainability for Python programs. We evaluated whether there is a correlation between the maintainability index and the cohesion metric for the classes in the subject programs. We also evaluated the effect of the module size on the accuracy of the maintainability index.